FAKTOR YANG MEMPENGARUHI MINAT GENERASI MILINEAL UNTUK MELANJUTKAN USAHATANI KELUARGA DI KECAMATAN MEJAYAN, KABUPATEN MADIUN - Widayanti, Sri; Ratnasari, Septilia; Mubarokah, Mubarokah; Atasa, Dita (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
In the agricultural sector, there was a decrease in the number of young workers, it was noted that in 2018 agricultural workers were dominated by workers aged 40 years and over by 55%. This is due to the lack of willingness of the younger generation to continue agricultural work as is done by their parents, as well as the unwillingness of parents for their children to do farming activities. The purpose of this study was to analyze the factors that influence the desire of the millennial generation to continue farming activities. The research was conducted in Mejayan Subdistrict by means of multiple stage cluster sampling areas selected Darmorejo village as the criteria for basic agricultural villages, Kaliabu as an industrial village, Mejayan village as a city village. The data analysis used in this research is binary logistic regression with independent variables including gender, motivation, experience, inheritance in the form of land, education, views on agriculture, income, land, community environment. The results showed that the variables that had a positive influence were motivation, inheritance in the form of land, the community environment, while those that had a negative effect were gender and views on agriculture.